2016
DOI: 10.15548/jt.v23i3.243
|View full text |Cite
|
Sign up to set email alerts
|

The Contributions of Quranic Tahfidz to Mental Health

Abstract: One of the miracles of the Qur'an is believed to influence the human's mental health, particularly to those who can memorize it. The Huffazh (Quranic Tahfidz) has been discussed in many verses, but only recently that scientific investigation gauged this issue, resulted in tremendous efforts to implant it among Muslim communities. The current study seeks to uncover the contribution of Quranic Tahfidz to mental health. Eight hundred and twenty-eight students studying Islamic Studies in the Faculty of Islamic Edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…These results suggest that there was a significant improvement in the academic performance of Huffaz after Hifz (memorization) though other factors, including educational and social, could also be responsible for this observation. It has also been suggested that memorizing and continuous challenging of the brain prevents memory loss and keeps the brain healthy (Kimiaee et al, 2012;Trinova and Wati 2016). In the second study, students of Islamic studies education and teacher training (with the same age bracket and similar social activities) were observed and asked to complete questionnaires on the contribution of Quranic Tahfidz (memorization) to mental health.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that there was a significant improvement in the academic performance of Huffaz after Hifz (memorization) though other factors, including educational and social, could also be responsible for this observation. It has also been suggested that memorizing and continuous challenging of the brain prevents memory loss and keeps the brain healthy (Kimiaee et al, 2012;Trinova and Wati 2016). In the second study, students of Islamic studies education and teacher training (with the same age bracket and similar social activities) were observed and asked to complete questionnaires on the contribution of Quranic Tahfidz (memorization) to mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Sejauh pengamatan penulis, tema ini belum begitu mendapat perhatian yang serius dari para pengkaji Al-Qur'an. Kajian lebih banyak menyoal tentang fenomena tahfiz dalam perspektif pendidikan secara umum sebagaimana yang dilakukan oleh Zulfitria (2016), Sugiati (2016), Ulfiah & Tarsono (2017), Keswara (2017), Akbar & Hidayatullah (2016), Rohmatillah & Shaleh (2018), Ansor (2017), Dalam perspektif psikologi, fenomena tahfiz juga pernah dikaji oleh Putri & Uyun (2017), Trinova & Wati (2016), Faza & Kustanti (2018), dan Romadlony & Jayadi (2019). Sementara dalam wacana sosiologi dan antropologi, fenomena tahfiz juga pernah diteliti oleh Sofyan (2015); Mubarok, Setiyowati & Mutiara (2018), dan Ahmad (2014).…”
Section: Pendahuluanunclassified
“…Berbeda dengan proses menghafal Al-Quran pada umumnya, proses menghafal Alquran pada tahfiz online dapat dilaksanakan kapan dan dimanapun berada. Santri dan guru masing-masing mampu menyetorkan dan mengoreksi hafalan melalui media sosial Whatsapp (Trinova, 2016).…”
Section: Pendahuluanunclassified